The Efforts of Islamic Religious Education Teachers in Developing Student Discipline - Della Maryati; Oyoh Bariah; Khalid Ramdani (EDUCATIO: Journal of Education)
This study aims to determine the efforts made by the teacher and the supporting and inhibiting factors of the teacher in developing the discipline of the students of SMPIT Al-Ridwan. The type of research used is a qualitative approach with a descriptive method. This research was conducted at SMPIT Al-Ridwan Telukjambe Timur Kab. Karawang. The results show that: (1) the teacher's efforts in developing student discipline at SMPIT Al-Ridwan through enforcement of regulations, giving punishments, giving rewards, and teacher consistency in motivating students, (2) factors supporting the efforts of teachers in developing student discipline at SMPIT Al -Ridwan through internal and external factors. (3) The inhibiting factors of the teacher's efforts in developing the discipline of SMPIT Al-Ridwan students through internal and external factors.